EFEKTIVITAS TEKNIK BERANTAI DALAM PEMBELAJARAN BERMAIN PERAN DI DALAM DRAMA - Putra, Andhika Amanda (2014)
This research entitled Efektivitas Teknik Berantai Dalam Pembelajaran Bermain Peran Di Dalam Drama. The obstacle's background of this research is the lack of teaching ability in an act play practice which has impacted to the student interests, knowledge and student incapability in learning an act play. These facts indicated by the researcher's finding; there are lot of students which never involved in act play, incapable of an act play, even lack of act and play knowledge. The aims of this research are (1) to get evidences from the result during the process of learning act play in the experimental class by teknik berantai; (2) showing that there are significant differences in learning act play before and after using teknik berantai. The methodology of this research uses One Group Pretest-Posttest quasi design. This experiment took place in SMP Negeri 10 Bandung while the subject of the research is VIIIE as the experimental class with 30 students. Based on the data research, the result findings are: 1) there is significant improvement of act play statistic in a class after the application of teknik berantai, while the before the application was 53,90 on average, while 80,96 is the statistic . Those numbers illustrate the effectiveness of using teknik berantai in act play class.